Servant Leadership and organizational culture: Implications for Organizational Citizenship Behavior with job satisfaction of accounting employees as a mediating variable in Manufacturing Companies in the City of Manado: Servant Leadership and organizational culture: Implications for Organizational Citizenship Behavior with job satisfaction of accounting employees as a mediating variable in Manufacturing Companies in the City of Manado - Sepang, Steify M.E; M. Merung, Harli M.E (JURNAL EKOBIS DEWANTARA, 2025)
Abstarct Human resources are individuals who act, manage, and execute various processes that play a role in improving organizational performance. One of the indicators of an organization's success is the presence of employees who are ready to undertake additional tasks or make extra efforts beyond their main responsibilities. This extra behavior is known as Organizational Citizenship Behavior. The purpose of this research is to determine the direct influence of servant leadership and organizational culture on organizational citizenship behavior, as well as to understand the indirect influence of servant leadership and organizational culture on organizational citizenship behavior mediated by employee job satisfaction. The data analysis technique in this study is Partial Least Square-Structural Equation Modeling (PLS-SEM). The results are that servant leadership has no significant effect on OCB, organizational culture has a significant effect on OCB, and servant leadership has no significant effect on OCB through employee job satisfaction, while organizational culture has a significant effect on OCB through employee job satisfaction.